City Branding: Macao - Rosa, A.; Panchapakesan, P. (International Conference on Business and Information, 2015)
As tourism industry is gaining importance worldwide, destinations vie with each other for tourists’ attention. There are many cities in the world which have successfully rebranded themselves in order to recover from the economic crises. Notwithstanding various initiatives taken by the government, Macao struggles to attract international tourist. This paper applies successful city branding strategies to Macao in identifying its current advantages and disadvantages as a preferred destination by employing SWOT methodology. It concludes by offering suggestions to successful repositioning of Macao as a world destination.